Immature Teratoma and Mature Cystic Teratoma - Sari, Nova Fenita; Nizar, RZ (Fakultas Kedokteran Universitas Andalas, 2021)
Introduction : Germ cell tumors arise from primordial germ cells and account for about 30% of all ovarian tumors. More than 95% of this group are benign dermoid cysts (mature cystic teratoma) and the remaining 5% are malignant. Ovarian teratomas represent 15% to 20% of ovarian germ cell tumors. Teratomas are classified as mature or immature and often consist of several embryological layers. While the mature type is benign, the immature type is more aggressive.Objective : Based on the above, this article will review about immature teratoma and mature cystic teratoma of the ovary. Material and methods : The method of writing this scientific paper is a literature review. The data used are sourced from relevant literature and in accordance with the topics discussed.Result : Teratomas are a common form of germ cell tumors. Teratomas are histologically defined as tumors containing tissue derived from all germ cell layers: ectoderm, mesoderm, and endoderm. Teratomas are classified as immature teratoma, mature teratoma and monodermal teratoma.Conclusion : Teratomas are usually asymptomatic and if there are symptoms, they tend to be non-specific. In patients with no residual tumor after surgery, the survival rate is 90-100%.Keywords: Teratoma, Immature Teratoma, Mature Cystic Teratoma